Gender Formulation in the Daily English Proverbs: A Discourse Analysis Study - Kzar, Ali Shimal (Cipta Pustaka Nusantara, 2025)
Proverbs are utilized in all languages to communicate particular messages. However, when proverbs are translated from one language to another, translation difficulties arise due to the cultural and linguistic connotations inherent to proverbs. The concept of power, and more specifically the social power of organizations or institutions, is typically considered to be one of the most important aspects of critical study on discourse. The role of women that is wife, daughter, mother or sister is being described and analyzed throughout discourse concepts such as power and social inequality. This study presents violence in critical discourse analysis of Proverbs of English to examine how power relationships of different genders are determined through linguistic choices in different languages/societies. The data of this study are 17 proverbs which have been selected from different sources about proverbs which are the most prominent in the English culture. Van Dijk (1988/1995) Model of Dominance and Power is used: When it comes to power problems, van Dijk (1995) tends to take a cognitive approach. The study has shown that Femininity can be seen as an established ideological term, portraying women as mere victims of subjugation.